2022
DOI: 10.7759/cureus.29843
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on the Effects of Vegetarian Diets on Coronary Heart Disease

Abstract: Coronary heart disease (CHD) is one of the leading causes of morbidity and mortality worldwide. Dietary modifications in the form of a vegetarian diet can perhaps be the key to the prevention and management of cardiovascular diseases. The aims of this review are to determine the association between a vegetarian diet and CHD, to compare the risk of CHD in different types of vegetarian diets, and to assess variability in the biochemical predictors of CHD in the various vegetarian diets. Our study inferred that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Also, we showed that red meat is the driver of the diet-attributable GHGEs among our population. Therefore, our positive association between diet-attributable GHGEs and MI could be explained in light of the existing literature associating red meat consumption with cardiovascular diseases [37][38][39][40][41] and plant-based diet with favorable cardiovascular outcomes [58][59][60][61][62]. However, we acknowledge the lack of consideration of the control for temperature variability across seasons and years in the current analysis because existing knowledge has shown that climate change itself has negative health consequences [63][64][65], including cardiovascular outcomes [65][66][67][68][69] and MI [70][71][72][73].…”
Section: Discussionmentioning
confidence: 89%
“…Also, we showed that red meat is the driver of the diet-attributable GHGEs among our population. Therefore, our positive association between diet-attributable GHGEs and MI could be explained in light of the existing literature associating red meat consumption with cardiovascular diseases [37][38][39][40][41] and plant-based diet with favorable cardiovascular outcomes [58][59][60][61][62]. However, we acknowledge the lack of consideration of the control for temperature variability across seasons and years in the current analysis because existing knowledge has shown that climate change itself has negative health consequences [63][64][65], including cardiovascular outcomes [65][66][67][68][69] and MI [70][71][72][73].…”
Section: Discussionmentioning
confidence: 89%
“…The descriptive systematic review by Babalola et al [ 3 ] reported that adherence to a plant-based diet was inversely related to heart failure risk and advantageous for the secondary prevention of CHD, particularly if started from adolescence. Another review by Agnoli et al [ 42 ], confirmed a lower incidence of CVDs associated with mixed vegetarian diets as compared to omnivorous diets.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the reduction of products of animal origin in favor of vegetarian ones has been suggested to reduce CVD and cancer risk [ 3 , 4 ]. Several major professional and scientific organizations encourage the adoption of vegetarian and vegan diets for the prevention and treatment of a range of chronic metabolic diseases such as atherosclerosis, type 2 diabetes, hypertension and obesity [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A vegetarian diet, especially when rich in raw plant foods, as well as whole grains and oilseeds, is related to the reduction of cardiovascular risk factors, such as obesity, hypertension, diabetes, and coronary artery disease, and may be a preventive factor for depression (Shen et al ., 2021; Babalola et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%